Family firm performance over the business cycle: A meta-analysis - Christopher Hansen; Jörn Hendrich Block; Matthias Neuenkirch (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2018)
The financial performance of family firms has been widely studied in the literature. Combining the results of 172 primary studies from 38 countries with data about business cycles, we investigated how family firm performance changes over the business cycle. Using meta-analytic estimation methods, we found that family firms slightly outperform nonfamily firms in both economically good and economically difficult times. For non-OECD countries, we found evidence for a countercyclical effect where the relative outperformance of family firms is higher in economically difficult times. No such cyclical effect was found for family firms in OECD countries. Our study extends the literature on how family firm performance depends on macroeconomic factors.
Keywords: 330; family firms; financial performance; meta-analysis; business cycle